Diamondoid naphthenic acids cause in vivo genetic damage in gills and haemocytes of marine mussels - Dissanayake, A.; Scarlett, Alan; Jha, A. (Springer, 2016)
Diamondoids are polycyclic saturated hydrocarbons that possess a cage-like carbon skeleton approaching that of diamond. These ‘nano-diamonds’ are used in a range of industries including nanotechnologies and biomedicine. Diamondoids were thought to be highly resistant to degradation, but their presumed degradation acid products have now been found in oil sands process-affected waters (OSPW) and numerous crude oils. Recently, a diamondoid-related structure, 3-noradamantane carboxylic acid, was reported to cause genetic damage in trout hepatocytes under in vitro conditions. This particular compound has never been reported in the environment but led us to hypothesise that other more environmentally relevant diamondoid acids could also be genotoxic. We carried out in vivo exposures (3 days, semi-static) of marine mussels to two environmentally relevant diamondoid acids, 1-adamantane carboxylic acid and 3,5-dimethyladamantane carboxylic acid plus 3-noradamantane carboxylic acid with genotoxic damage assessed using the Comet assay. An initial screening test confirmed that these acids displayed varying degrees of genotoxicity to haemocytes (increased DNA damage above that of controls) when exposed in vivo to a concentration of 30 μmol L−1. In a further test focused on 1-adamantane carboxylic acid with varying concentrations (0.6, 6 and 30 μmol L−1), significant (P < 0.05 %) DNA damage was observed in different target cells (viz. gills and haemocytes) at 0.6 μmol L−1. Such a level of induced genetic damage was similar to that observed following exposure to a known genotoxin, benzo(a)pyrene (exposure concentration, 0.8 μmol L−1). These findings may have implications for a range of worldwide industries including oil extraction, nanotechnology and biomedicine.